La descentralización fiscal y su efecto en la corrupción. El caso de los países en desarrollo por América Latina - Pilamunga Pomaquero, Joel Alexander (2023)
ABSTRACT: The main objective is to respond to the influence of decentralization on the perception of corruption, with the case study of the developing countries of Latin America, period 2010 to 2020, therefore, a database was built for each of the countries to be developed, so that the use of panel data is given, that is, cross-sectional and time series where the dependent variable is corruption and with respect to fiscal decentralization, six indicators are considered, the model to be estimated is two models different in terms of heterogeneity, the first case being due to ordinary least squares and the second due to generalized least squares. To select the model that best responds to heterogeneity, the Hausman test is applied, obtaining that the first 3 decentralization variables were not significant and in the case of fiscal decentralization variables there were 3 cases in which negative signs were obtained, that the greater the transfers, the less corruption and their perception becomes.